2013
DOI: 10.1002/rog.20011
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Methane on Earth

Abstract: [1] Over the last 30 years, geochemical research has demonstrated that abiotic methane (CH 4 ), formed by chemical reactions which do not directly involve organic matter, occurs on Earth in several specific geologic environments. It can be produced by either high-temperature magmatic processes in volcanic and geothermal areas, or via low-temperature (<100 C) gas-water-rock reactions in continental settings, even at shallow depths. The isotopic composition of C and H is a first step in distinguishing abiotic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
452
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 484 publications
(464 citation statements)
references
References 171 publications
9
452
2
1
Order By: Relevance
“…Several subsequent experimental studies confirmed that abiotic reduction of dissolved CO 2 to CH 4 is sluggish at temperatures as low as 300°C, even in the presence of highly elevated H 2 concentrations, except when NiFe alloy was present (16,(18)(19)(20)(21). Additional experiments with 13 C-labeled inorganic carbon compounds also confirmed that background sources are a ubiquitous contributor to CH 4 in experimental fluidrock studies using olivine or other minerals, with abundance that often far exceeds that of bona fide synthesis products (18,19,28).…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…Several subsequent experimental studies confirmed that abiotic reduction of dissolved CO 2 to CH 4 is sluggish at temperatures as low as 300°C, even in the presence of highly elevated H 2 concentrations, except when NiFe alloy was present (16,(18)(19)(20)(21). Additional experiments with 13 C-labeled inorganic carbon compounds also confirmed that background sources are a ubiquitous contributor to CH 4 in experimental fluidrock studies using olivine or other minerals, with abundance that often far exceeds that of bona fide synthesis products (18,19,28).…”
mentioning
confidence: 76%
“…Several recent reports have claimed observation of abiotic formation of methane during low-temperature serpentinization of olivine-rich rocks during laboratory experiments. However, using 13 C-labeled carbon sources, this study shows that the methane observed in such experiments is predominantly derived from background sources rather than abiotic synthesis. Conversely, more rapid production of methane is observed when an H 2 -rich vapor phase is present within the reaction vessel.…”
mentioning
confidence: 81%
See 3 more Smart Citations